Effect of Piezoresistive Behavior on Electron Emission from Individual Silicon Carbide Nanowire - Peng Zhao; Yu Zhang; Shuai Tang; Runze Zhan; Juncong She; Jun Chen; Ningsheng Xu; Shaozhi Deng (Nanomaterials, 2019)
The excellent properties of silicon carbide (SiC) make it widely applied in high-voltage, high-power, and high-temperature electronic devices. SiC nanowires combine the excellent physical properties of SiC material and the advantages of nanoscale structures, thus attracting significant attention from researchers. Herein, the electron vacuum tunneling emission characteristics of an individual SiC nanowire affected by the piezoresistive effect are investigated using in situ electric measurement in a scanning electron microscope (SEM) chamber. The results demonstrate that the piezoresistive effect caused by the electrostatic force has a significant impact on the electronic transport properties of the nanowire, and the excellent electron emission characteristics can be achieved in the pulse voltage driving mode, including lower turn-on voltage and higher maximum current. Furthermore, a physical model about the piezoresistive effect of SiC nanowire is proposed to explain the transformation of electronic transport under the action of electrostatic force in DC voltage and pulsed voltage driving modes. The findings can provide a way to obtain excellent electron emission characteristics from SiC nanowires.